2018
DOI: 10.1101/272245
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Most regulatory interactions are not in linkage disequilibrium

Abstract: Linkage disequilibrium (LD) and genomic proximity are commonly used to map non-coding variants to genes, despite increasing examples of causal variants outside the LD block of the gene they regulate. We compared chromatin contacts in 22 cell types to LD across billions of pairs of loci in the human genome and found no concordance, even at genomic distances below 25 kilobases where both tend to be high. Gene expression and ontology data suggest that chromatin contacts identify regulatory variants more reliably … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…TADs are defined by 3D chromatin interactions in cell nuclei whereas LD reflects historical events for a given human sample. We confirmed that TADs and LD blocks identify different genomic regions 17,46 . Fifth, we conducted evolutionary analyses for brain FIREs and found that these regions have stronger evidence for ancient and recent positive selection, less population differentiation, and fewer singleton/doubleton single nucleotide variants (Table S5).…”
Section: General Properties Of Chromatin Organization In Brainsupporting
confidence: 74%
“…TADs are defined by 3D chromatin interactions in cell nuclei whereas LD reflects historical events for a given human sample. We confirmed that TADs and LD blocks identify different genomic regions 17,46 . Fifth, we conducted evolutionary analyses for brain FIREs and found that these regions have stronger evidence for ancient and recent positive selection, less population differentiation, and fewer singleton/doubleton single nucleotide variants (Table S5).…”
Section: General Properties Of Chromatin Organization In Brainsupporting
confidence: 74%
“…These distinct data types-often derived in different laboratories in different samples-show significant overlap in regulatory predictions (Gusev et al, 2018). This is in contrast to comparisons relying on LD blocks or the assignment by the closest gene, where the overlaps with methods that directly assess chromatin are less substantial (Short et al, 2018;Whalen and Pollard, 2018).…”
Section: From Variant To Genementioning
confidence: 99%
“…A complicating factor is that assigning even well-annotated genomic regions to specific genes is not as simple as choosing the closest gene or genes containing variation that is highly correlated with the associated SNPs, which is usually the default approach (Whalen et al, 2016;Won et al, 2016). Rather, as suggested by studies of brain eQTL (Battle et al, 2017;Hauberg et al, 2017) and chromatin structure (de la Torre-Ubieta et al, Won et al, 2016), nearly half of the target genes of human regulatory variation are not in genomic loci defined by linkage disequilibrium (LD) (Whalen and Pollard, 2018) (Table 3). Thus, ''4D mapping'' of chromatin interactions (i.e., brain regions across developmental time) is critical for understanding the functional relationships of regulatory regions to genes (Dekker et al, 2017).…”
Section: From Variant To Genementioning
confidence: 99%
“…Finally, evidence has recently been published that the targets of identified non-coding variants are occasionally not within linkage disequilibrium blocks in the genome (Whalen and Pollard, 2018). This does not necessarily conflict with our results, since we identify hits at only 38 of 75 examined loci and provides an intriguing direction for further work that may elucidate how Our data shows that gene-centric screens are valuable for GWAS follow-up.…”
Section: Discussionmentioning
confidence: 99%